THEORETICAL ASPECTS OF THE STUDY OF THE DEVELOPMENT OF THE REFLEXIVE POSITION OF STUDENTS IN THE CONDITIONS OF DISTANCE EDUCATION - Nuraly, A.Zh. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
Today, the main task of teachers is no longer just the transfer of information, but the formation of the ability to learn. The concept of «learning ability» includes the consistent development of various educational activities, including the development of reflection-the neoplasm of school-age children in the conditions of distance education. Purpose: to study the theoretical foundations of the study of the development of the reflexive position of students in the conditions of distance education
Keywords: distance learning; reflexive position; self-reflection; reflexivity